2020
DOI: 10.1186/s12917-020-02292-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genotypic identification of Cryptosporidium spp. and Enterocytozoon bieneusi in captive Asiatic black bears (Ursus thibetanus) in Heilongjiang and Fujian provinces of China

Abstract: Background: Cryptosporidium and Enterocytozoon bieneusi are two important pathogens with zoonotic potential that cause enteric infections in a wide range of hosts, including humans. Both are transmitted from animals to humans by direct contact or through contaminated equipment. Bears are frequently found in Chinese zoos as ornamental animals as well as farmed as commercial animals, and are therefore in close contact with zoo-or farmkeepers, but the prevalence and zoonotic potential of Cryptosporidium and E. bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Higher proportion of Cryptosporidium prevalence has been reported previously in wild and domestic mammals in South Africa (14%, 8/56) and in free-living wild felids in Brasil (15%, 2/13) (Lukášová et al, 2018;Holsback et al, 2013). Fewer studies also revealed lower rates of Cryptosporidium in wild and captive reptiles in USA 3% (15/528) and in captive Asiatic black bears (Ursus thibatenus) in China 2.4% (4/218) (Upton et al, 1989;Wang et al, 2020). In Italy, parasitic investigation in mammals of two zoological gardens reported the prevalence of Cryptosporidium in carnivores (10%), primates (66.7%) and artiodactyls (25%) (Fagiolini et al, 2010).…”
Section: Discussionmentioning
confidence: 81%
“…Higher proportion of Cryptosporidium prevalence has been reported previously in wild and domestic mammals in South Africa (14%, 8/56) and in free-living wild felids in Brasil (15%, 2/13) (Lukášová et al, 2018;Holsback et al, 2013). Fewer studies also revealed lower rates of Cryptosporidium in wild and captive reptiles in USA 3% (15/528) and in captive Asiatic black bears (Ursus thibatenus) in China 2.4% (4/218) (Upton et al, 1989;Wang et al, 2020). In Italy, parasitic investigation in mammals of two zoological gardens reported the prevalence of Cryptosporidium in carnivores (10%), primates (66.7%) and artiodactyls (25%) (Fagiolini et al, 2010).…”
Section: Discussionmentioning
confidence: 81%
“…In the current study, the results of the microscopic prevalence are higher than the other two methods, which may be due to misdiagnosis with other elements and microorganisms. Nevertheless, nowadays molecular techniques are considered the gold standard for detection and differentiation of microsporidia at the species/genotype levels [63,64]. The main advantage of molecular methods is higher sensitivity and specificity, along with easier interpretation [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…E. bieneusi and Cryptosporidium spp. are the common zoonotic enteric pathogens responsible for a majority of parasitic diarrhea diseases worldwide ( Qi et al., 2015 ; Zhang X. et al., 2018 ; Zhao et al., 2018 ; Wang S. N. et al., 2020 ). Both of them can infect humans and a wide variety of animals (e.g., rodents) ( Wang et al., 2013 ; Zhao et al., 2018 ; Li and Xiao, 2020 ; Wang S. N. et al., 2020 ) mainly through water-borne and food-borne routes ( Wang et al., 2013 ; Zhao et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…are the common zoonotic enteric pathogens responsible for a majority of parasitic diarrhea diseases worldwide ( Qi et al., 2015 ; Zhang X. et al., 2018 ; Zhao et al., 2018 ; Wang S. N. et al., 2020 ). Both of them can infect humans and a wide variety of animals (e.g., rodents) ( Wang et al., 2013 ; Zhao et al., 2018 ; Li and Xiao, 2020 ; Wang S. N. et al., 2020 ) mainly through water-borne and food-borne routes ( Wang et al., 2013 ; Zhao et al., 2018 ). In general, healthy people infected with both pathogens are asymptomatic or manifest symptoms of self-limiting diarrhea.…”
Section: Introductionmentioning
confidence: 99%